Composition of the Fecal Microbiota of Piglets at Various Growth Stages - Yang, Yang; Liu, Yadan; Liu, Juan; Wang, Haizhen; Guo, Yulong; Du, Min; Cai, Chunbo; Zhao, Yan; Lu, Chang; Guo, Xiaohong; Cao, Guoqing; Duan, Zhibian; et al. (Frontiers in Veterinary Science, 2021)
Gastrointestinal (GI) microbiota plays an important role in promoting growth in piglets. However, studies on microbiota composition at various growth stages are lacking. We measured body weights of Jinfen White and Mashen piglets every seven days and collected their fecal samples by rectal swabbing at nine time points during suckling (1-28 days) and nursery (35-70 days) stages to gain insight into microbiota variability during piglet growth. The fecal microbiota was characterized via 16S rRNA gene sequencing to analyse effects of microbial diversity on piglet growth and development preliminarily. The results showed that although the two breeds of piglets have similar body weights at birth, weaned Jinfen White piglets demonstrated a significantly greater body weight and daily weight gain than weaned Mashen piglets (P< 0.01). A total of 1,976 OTUs belonging to 27 phyla and 489 genera were uncovered, in which the highest numbers of OTUs belongs to phyla Firmicutes and Bacteroidetes. Lactobacillus, Bacteroides and Prevotellaceae NK3B31 groups accounting for 12.4%, 8.8%, and 5.8% of OTUs, respectively, showed relatively high abundance at the genus level. Nine sampling time points were divided into three growth stages, namely, immediate postfarrowing (1 day old), suckling (7, 14, and 21 days old) and nursery (28, 35, 49, 63, and 70 days old), on the basis of the results of microbial diversity, principal coordinate and co-occurrence network analyses. In addition, it identified 54 discriminative features in the microbiota between two breeds of piglets by LEfSe analysis, in which 17 genera enriched in microbiota community of Jinfen White piglets. Finally, abundances of 29 genera showed significant positive correlations with body weights and daily weight gain of piglets. Conversely, abundances of 12 genera demonstrated significant negative correlations with body weights of piglets. Results of our study will provide a theoretical basis for succession patterns in fecal microbiota of piglets and suggest the need for meticulous management of piglets in pig production.